Screening of Diabetic Retinopathy in a Diabetic Medical Center - Muhammad Imran Hasan Khan, Saher Khalid, Mohammad Moin (Pakistan Journal of Ophthalmology, 2015)
Purpose: To estimate the prevalence of diabetic retinopathy on the posterior pole of newly diagnosed diabetic patients using a non-mydriatic fundus camera. Materials and Methods: Descriptive case series of 822 patients (male: female 29.4:70.6), screened during 10 months (August 2014-May 2015) was done in Diabetes Endocrine and Metabolic Centre (DEMC) using a single posterior pole photograph centered on the fovea using a non-mydriatic fundus camera. Without pupil dilation, grading of diabetic retinopathy was done using Airlie House classification which divides diabetic retinopathy (DR) into 5 grades i.e. background DR, pre-proliferative DR, proliferative DR, maculopathy and advanced disease. After grading, patients were referred to eye outpatient department for further management. Newly diagnosed diabetics, including pregnant and hypertensive patients were studied. Patients with hazy media, cataracts and evisceration were excluded. Results: 170 (20.6%) out of 822 patients showed diabetic retinopathy in which 10 patients had type 1 (5.8%) while 160 patients (94.1%) had type 2 diabetes at presentation. Highest distribution of diabetic retinopathy belonged to the age group 50 (21.7%) (Mean 50.4, Std. Deviation 9.76). Out of 170, 98 patients showed background diabetic retinopathy (57.6%), 31 patients showed preproliferative (18.25%), 20 patients showed proliferative diabetic retinopathy (PDR) (11.7%), 12 showed maculopathy (7.05%) and only 9 patients (5.2%) showed advanced disease. Patients with vitreous hemorrhage, tractional retinal detachment and neovascular glaucoma were considered as having advanced disease. These results were totally based on posterior pole findings of diabetic patients. Out of 170 patients, 8 had nephropathy (4.7%), 122 had neuropathy (71.7%) and 99 patients (58.2%) had preexisting hypertension. Conclusion: Fundus photograph with a non mydriatic camera in a diabetic medical center is a very useful tool to guide patients for early treatment, to prevent blindness. Key words: Diabetes Mellitus, Fundus camera, Diabetic retinopathy screening.